2017
DOI: 10.1016/j.sjdr.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of preventive dental knowledge among adult patients seeking dental care in Riyadh, Saudi Arabia

Abstract: Aim: to evaluate the current knowledge about oral health and preventive dentistry among adults seeking dental care in Riyadh, Saudi Arabia. Materials and Methods:A cross-sectional descriptive study was conducted in which 900 questionnaires were randomly distributed to adults seeking dental care in all health settings in Riyadh; 450 questionnaires were distributed in each of the governmental and the private sectors. The questionnaire included questions regarding socio-demographic factors (age, education, occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…AlSadhan et al conducted a study on adults seeking dental care in public and private sectors in Riyadh, Saudi Arabia, and showed that dentist (49.3%) was the main source of oral health care information, followed by television (36.3%), books (15%) and family (12%). 38 However, due to lockdowns as a result of the pandemic, family and friends (62.5%), and social media (57.6%) were the most common sources of oral health information in the present study. Less than 1% of participants indicated dentists as the source of oral health instruction which points out to a big interpersonal communication gap between dentists and their patients in Dammam.…”
Section: Discussionmentioning
confidence: 62%
“…AlSadhan et al conducted a study on adults seeking dental care in public and private sectors in Riyadh, Saudi Arabia, and showed that dentist (49.3%) was the main source of oral health care information, followed by television (36.3%), books (15%) and family (12%). 38 However, due to lockdowns as a result of the pandemic, family and friends (62.5%), and social media (57.6%) were the most common sources of oral health information in the present study. Less than 1% of participants indicated dentists as the source of oral health instruction which points out to a big interpersonal communication gap between dentists and their patients in Dammam.…”
Section: Discussionmentioning
confidence: 62%
“…Dentists should also provide written information on post extraction complications to prevent it. Some of the researchers pointed out that more than half of their patients preferred both verbal and written information [12]. This cross-sectional study was performed to assess the PEPK among the patients seeking dental care at dental clinic of Taibah University College of Dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers reported females were more conscious about their oral health and they used to listen very carefully and practiced it [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the rural study setting where the parents are comparatively less educated and also due to lesser number of qualified dental professionals who are the crucial source of spreading awareness in their society. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%